2003
DOI: 10.1136/jcp.56.11.821
|View full text |Cite
|
Sign up to set email alerts
|

Fine needle aspiration cytology in the diagnosis of uncommon types of lymphoma

Abstract: Aims: Fine needle aspiration (FNA) cytology is an accepted means of diagnosing and typing common forms of lymphoma, particularly small lymphocytic lymphoma, follicular lymphoma, and large B cell lymphoma. However, its usefulness for diagnosing less common forms of lymphoma is not clearly established and this study was designed to examine this. Methods: The study reviewed the FNAs of suspected lymphomas collected over a period of approximately five years. Results: FNA samples were available for 138 definite lym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 13 publications
0
43
0
2
Order By: Relevance
“…However, other studies have not been as definitive. [15] A study by Mayall et al found the diagnostic accuracy of FNA lower, with HL being particularly difficult to diagnose by FNA [15]. Thus, the role of FNA in the diagnosis of pediatric HL requires further study.…”
Section: Discussionmentioning
confidence: 97%
“…However, other studies have not been as definitive. [15] A study by Mayall et al found the diagnostic accuracy of FNA lower, with HL being particularly difficult to diagnose by FNA [15]. Thus, the role of FNA in the diagnosis of pediatric HL requires further study.…”
Section: Discussionmentioning
confidence: 97%
“…However, this theoretical drawback is rarely encountered [16,28] . Also, primary diagnosis of uncommon lymphomas may be compromised by small samples obtained by needle biopsy, and as with biopsies negative for lymphoma, surgical intervention may be required [16,29] . Indeed, some subtypes of malignant lymphoma might not be definitely diagnosed and categorized by CT-guided core-needle biopsy alone [29,30] .…”
Section: Discussionmentioning
confidence: 99%
“…Also, primary diagnosis of uncommon lymphomas may be compromised by small samples obtained by needle biopsy, and as with biopsies negative for lymphoma, surgical intervention may be required [16,29] . Indeed, some subtypes of malignant lymphoma might not be definitely diagnosed and categorized by CT-guided core-needle biopsy alone [29,30] . Ben-Yehuda et al [31] , suggested that the most problematic category is mixed small-and large-cell NHL, because of the difficulty in making a reliable assessment of the relative number of large cells present and distinguishing diffuse from nodular patterns in these cases.…”
Section: Discussionmentioning
confidence: 99%
“…After solidification, it is flooded by formalin and picked up, dried out, and processed. The cells in this block are ­densely packed and suitable for immunohistochemistry [18, 19]. …”
Section: Vapour-fixed Fine Needle Aspiration Methodsmentioning
confidence: 99%